THIOSULFATES IN WATER OF THE BLACK SEA - Sovga Y.Y.; Solov'yeva L.V. (My University, 1987)
There are two hypotheses regarding thiosulfates in the Black Sea: a) that they are an intermediate product of the oxidation of hydrogen sulfide and b) that they are an intermediate product of the reduction of sulfates to hydrogen sulfide. Based on the data presented, the authors conclude that in distribution type I the maximum thiosulfate concentration occurs at depths of 200 to 500 m. The vertical distributions for this type exhibit one or two peaks, as yet unexplained, below these depths, and thiosulfates are not found in the bottom water. This type of distribution occurs at the centers of the western and eastern halistases. In distribution type II the thiosulfate peak occurs at depths of 300 m and in the bottom water. Distribution type III shows a continuous increase in the thiosulfate concentration from depths of 300 to 400 m to the bottom, with a peak at a depth of 1400 m or in the bottom water.